Posyandu sebagai Soft Power Indonesia dalam Diplomasi Kesehatan Global - Taufik Hidayat; Affabile Rifawan; Yan Mulyana; Adityo Darmawan Sudagung (Intermestic: Journal of International Studies, 2017)
This reasearch article aims to know and describe the effort of Posyandu revitalization as one of Indonesian way to increase soft power in conducting global health diplomacy. Using Qualitative Methods, also global health, Posyandu, public-private partnership, and soft power concepts, research find that Indonesia has done a lot of health diplomacy in the international arena. The improvement of the Posyandu model with the private sector can be one of Indonesia's softt power in conducting diplomacy in the global health sector.